The Effect of Problem-Project Based Learning on Critical and Collaborative Thinking Skills of Students of SD Negeri 2 Darmayasa - Ika Wulandari; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This study aims to determine the effect of Problem-Project Based Learning on Critical and Collaborative Thinking Skills of Students of SD Negeri 2 Darmayasa in the 2023/2024 academic year. This study uses a quantitative research approach, with an associative research type (relationship), and uses quantitative analysis methods (data in the form of numbers). Data on critical and collaborative thinking skills were collected through observation using an assessment instrument in the form of a rubric. The sample in this study totalled 16 students. The results of statistical testing between the IPAS Learning indicator and the prob-probl learning model approach to the Critical Thinking Ability variable have tcount (3.854) and ttable (2.776), meaning tcount> ttable. For the effect of the prob-probl learning model approach on the collaboration ability variable, tcount = (3.559) and ttable (2.776), meaning tcount> ttable. Based on the results of this study, it shows that there is an effect of the influence of Problem-Project Based Learning on the ability to think critically and collaboratively of fifth grade students of SD Negeri 2 Darmayasa in the 2023/2024 academic year.